Aerial choreography : low trapeze movement andamp; dance - (:unkn) unknown (Seattle, Wash. : University of Washington School of Drama, 2018)
Demonstrates his choreography which utilizes the low-flying triangular trapeze; Drama 401 colloquium; Recorded at the University of Washington, Seattle, on May 18, 1992; Demonstrates his choreography which utilizes the low-flying triangular trapeze.
Keywords: Davidson, Robert; Choreographers; Aerialists; Dance; Aerialists; Choreographers; Dance